Discovery and Development of Caffeic Acid Analogs as Versatile Therapeutic Agents - Yi Mou; Shuai Wen; Hong-Kai Sha; Yao Zhao; Li-Juan Gui; Yan Wang; Zheng-Yu Jiang (MDPI AG, 2024)
Caffeic acid (CA) is a polyphenolic acid compound widely distributed in plant seeds. As natural compounds with high research interest, caffeic acid and its derivatives show good activity in the treatment of tumors and inflammation and have antibacterial properties. In recent years, caffeic acid derivatives have been studied extensively, and these derivatives fall roughly into three categories: (1) caffeic acid ester derivatives, (2) caffeic acid amide derivatives, (3) caffeic acid hybrids. These caffeic acid analogues exert mainly antibacterial and antioxidant activities. Among the caffeic acid analogues summarized in this paper, compounds 1g and CAP10 have good activity against Candida albicans, and their MIC50 is 32 µg/mL and 13 μM, respectively. In a DPPH assay, compounds 3k, 5a, CS2, Phellinsin A and 8j showed strong antioxidant activity, and their IC50 values are 18.6 μM, 67.85 μM, 40.29 μM, 0.29 ± 0.004 mM, 4774.37 ± 137.20 μM, respectively. Overall, compound CAP10 had the best antibacterial activity and compound 3k had the best antioxidant activity. This paper mainly summarizes and discusses some representative caffeic acid analogs, hoping to provide better drug design strategies for the subsequent development of caffeic acid analogs.